Little’s Law and Educational Inequality: A Comparative Case Study of Teacher Workaround Productivity - Keppler, Samantha M. (Management Science, 2024)
In this paper, we explore an employee workaround widespread in K–12 schools: compensating for insufficient funding with partnerships to nonprofit organizations (NPOs). We take an equity perspective and ask the following questions. (i) How do partnering workarounds differ across schools with different levels of socioeconomic advantage? (ii) What can education and NPO leaders do to ensure these workarounds do not exacerbate educational inequities? To answer these questions, we use Little’s Law: a school’s long-run average number of resource-supplementing partnerships (L) is a function of its average annual partnership formation rate (λ) and partnership cycle time (W). We collect and analyze interview (n = 62) and survey (n = 140) data from six strategically sampled schools with different levels of socioeconomic advantage to compare differences in λ and W and understand the implications for educational equity. We find wealthier schools have higher λ, making them more productive. We also find schools have equal W independent of wealth, but this problematically amplifies differences in λ. The difference in partnering productivity translates to educational inequities. We find that poorer schools report about 35% greater utility per partnership, but that is not enough to offset the disadvantage of fewer partnerships. Moreover, we find that differences in partnering productivity are particularly large for curricular partnerships, which are harder for poorer schools to form because of the high demand for wrap-around partnerships. Our findings contribute new knowledge on workarounds which supplement organizational resources and on the relationship between workarounds and equity. This paper was accepted by Jay Swaminathan, operations management. Funding: This work was supported by the National Science Foundation [Grant 1344266]. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2023.4829 .